Economic Impacts of China's Accession to the World Trade Organization - Martin, Will, 1953- 1953- (The World Bank, 2003)
Ianchovichina and Martin present estimates of the impact of accession by China and Chinese Taipei to the World Trade Organization. China is estimated to be the biggest beneficiary, followed by Chinese Taipei and their major trading partners. Accession will boost the labor-intensive manufacturing sectors in China, especially the textiles and apparel sector that will benefit directly from the removal of quotas on textiles and apparel exports to North America and Western Europe. Consequently, developing economies competing with China in third markets may suffer relatively small losses. China has already benefited from the reforms undertaken between 1995 and 2001 (US